Analisis Penilaian Kinerja Pegawai Bank Sumsel Babel Menggunakan Key Performance Indikator - Nurhasmul, Hidayat; Oktarina, Tri (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2025)
This study aims to analyze the performance appraisal of bank sumsel babel employees using key perfomance indicators. This research uses descriptive qualitative approach. The subjects in this study were employees of Bank Sumsel Babel Sekayu Branch Determination. Data collection in this study includes observation, interviews, and documentation. Samples representing the population were selected by purposive sampling method. Analysis techniques in this study using qualitative descriptive analysis techniques. From the results of the study it can be concluded that the assessment of employee performance at Bank Sumsel Babel Sekayu Branch using key perofrmance indicators is carried out for all employees, which is carried out at the beginning of the year until the end of the year. KPIs have a significant effect, for example on success factors and certainly have a positive effect on employee performance appraisals. Monitoring and evaluation of KPIs at Bank Sumsel Babel Sekayu Branch is carried out twice a year, namely in Semester I in the period from January to July. While in Semester II in the period from January to December (one full year).